Phagocytosis : microbial invasion - Gordon, Siamon (Advances in cell and molecular biology of membranes and organelles, 1999)
The present volume focuses on microbial invasion strategies of pathogen uptake. An accompanying volume (Vol. 5) in the series presents the phagocytic process from the viewpiont of the host cell. This field of study is growing rapidly after a somewhat slow start over recent decades. This collection of invited chapters attempts to reflect current research and brings together cell biologists, microbiologists, and immunologists wiht disthemes, hopefully like a symphony rather than a boring catalogue. It will be evident that editorial bias favors intracellular parasitism and medically important organisms. The neutrophil is far more than a supporting player to the macrophage and some attempt is made to remind the reader of some of its unique skills. To retain a manageable size, the emphasis is on relatively early events such as mutual recognition, cell entry, and response, rather than on longterm changes in gene expression by either host cell or pahtogen. Viruses are excluded not because of lack of importance but because of somewhat different research approaches, although it is becoming increasingly clear that large viruses (e.g. Vaccinia) and Listeria monocytogenes, share common strategies in invasion and intercellular spread.